The mental health of Korean immigrants in São Paulo, Brazil Saúde mental dos imigrantes coreanos em São Paulo, Brasil - Sam Kang; Denise Razzouk; Jair Jesus de Mari; Itiro Shirakawa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
This study investigated the frequency of lifetime mental disorders among Korean immigrants in the city of São Paulo, Brazil. Snowball sampling with multiple focuses was used to recruit Korean immigrants older than 18 years and living in São Paulo. A total of 324 Korean immigrants were selected and their mental status was evaluated using a structured interview, namely the Portuguese or the Korean version of the Composite International Diagnostic Interview 2.1. The diagnoses of mental disorders were made according to the ICD-10. The frequency of any lifetime psychiatric disorder was 41.9%. The frequencies of main disorders were: anxiety disorder, 13% (post-traumatic stress disorder, 9.6%); mood disorder, 8.6%; somatoform disorders, 7.4%; dissociative disorder, 4.9%; psychotic disorder, 4.3%; eating disorder, 0.6%; any substance (tobacco, alcohol, drugs) use disorder, 23.1%. The frequency of any psychiatric disorder except alcohol and tobacco use disorders was 26.2%. Korean immigrants have more psychiatric disorders than the Korean population in Korea, particularly post-traumatic stress disorder, and almost the same rate as the Brazilian population. Mental health authorities should promote a healthier integration and the development of culturally sensitive mental health programs for Korean immigrants. Este estudo verificou a freqüência de transtornos psiquiátricos em uma comunidade de imigrantes coreanos na cidade de São Paulo, Brasil. A amostragem snowball com vários focos foi utilizada para contatar os imigrantes coreanos, acima de 18 anos e residentes em São Paulo. Foram selecionados 324 sujeitos, cuja saúde mental foi avaliada por meio de uma entrevista estruturada, Composite International Diagnostic Interview 2.1, nas versões em português e coreano. Foi utilizado o critério de diagnóstico CID-10. A freqüência de algum diagnóstico psiquiátrico na vida foi de 41,9%. As freqüências de principais diagnósticos na vida foram: transtornos de ansiedade, 13% (transtorno de estresse pós-traumático, 9,6%); transtornos do humor, 8,6%; transtornos somatoformes, 7,4%; transtornos dissociativos, 4,9%; transtornos psicóticos, 4,3%; transtornos alimentares, 0,6%; transtornos decorrentes de substâncias (álcool, tabaco ou drogas), 23,1%. A freqüência de diagnósticos psiquiátricos na vida, excluindo-se os decorrentes de álcool e tabaco, foi de 26,2%. Os imigrantes coreanos apresentam mais transtornos psiquiátricos do que a população coreana na Coréia, especialmente transtorno de estresse pós-traumático, e uma taxa semelhante à encontrada na população brasileira. As autoridades de saúde mental devem promover uma integração mais saudável por meio de programas culturalmente sensíveis aos imigrantes coreanos.